Neuropsychological assessment of impulsive behavior in abstinent alcohol-dependent subjects - Salgado,João Vinicius (2009)
OBJECTIVE: Poor impulse control is thought to be one of the characteristics of alcohol addiction. The capacity to remain abstinent may be linked to cognitive bias related to three dimensions of impulsivity: motor, non-planning, and attentional impulsivity. The aim of this study was to evaluate the neuropsychological profile related to these impulsivity dimensions in alcohol-dependent patients within 15 -120 days of abstinence. METHOD: We compared 31 alcohol-dependent patients to 30 matched healthy controls regarding their performances on the Continuous Performance Task, the Iowa Gambling Test, and the Wisconsin Card Sorting Test, each of which is thought to tax primarily one of the three dimensions of impulsivity just outlined. RESULTS: When compared to controls, alcohol-dependent patients presented more commission errors on the Continuous Performance Task; made more disadvantageous choices on the Iowa Gambling Test; and made more perseverative errors on the Wisconsin Card Sorting Test. There was no significant correlation between performance on these tests and the length of abstinence. CONCLUSIONS: These results suggest that deficits related to motor, non-planning and attentional components of impulsivity exist in alcohol-dependent patients, in the period immediately after acute alcohol withdrawal. These results may help guide interventions designed to prevent the risk of relapse in alcohol-abstinent patients.